Redefining the value proposition through green promotions and green corporate image in the era of Industrial Revolution 4.0: A study of Gen Y green consumers in Malaysia - Bathmanathan V.; Rajadurai J. (Inderscience Publishers, 2023)
Sales; Surveys; Corporate images; Digital disruption; Green marketing; Green purchasing; Industrial revolutions; Green manufacturing; business development; consumption behavior; corporate strategy; decision analysis; digital mapping; industrial regulation; marketing; policy making; Malaysia